COLLABORATIVE LEARNING AND PROBLEM-BASED LEARNING IN TEACHING SPEAKING - Bestari Retno Wardani; Intan Satriani (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
The purposes of this research is to investigate the achievement and improvement of students’ English-speaking ability at the eleventh-grade students of SMK 4 LPPM RI Padalarang. The researcher used quasi-experimental research design in this research. The instruments are tests. The tests were done twice to the experimental class and the control class. They are pre-test and post-test. The data were calculated using Microsoft Office Excel 2019 and IBM SPSS 25. There are 30 students in each class. The total of the population is 60 students. The results of the research showed that from the implementation of Cooperative Script Method at the eleventh-grade students of SMK 4 LPPM RI Padalarang, the students’ English-speaking ability are improved significantly. It can be seen from the post-test mean score achievement. It can be concluded that the students’ English-speaking ability improvement who learned using Cooperative Script Method are better than students who learned using Problem-Based Learning. The implementation of Cooperative Script Method is effective in teaching speaking.